Pastoral care of Civil Aviation. Pastoral recommendations - NECEL, WOJCIECH (Prawo Kanoniczne, 2017)
The document in question (Catholic Civil Aviation Pastoral Directives) is an expression of care the Church has for the faithful in their specific life and professional situations. The canonical and pastoral indications contained in the Directives are intended to identify the persons to whom the Civil Aviation Ministry is directed as well as those responsible for this kind of pastoral care, and indicate the necessary structures for this form of apostolic activity. According to the guidelines an important element of this pastoral care, so at domestic as well as international airports, is to open itself to those to whom this form of apostolate is directed and to all those in need of help while staying at the airport.